Medical examination and preparation of the medical documentation in the case of victims of crimes of a sexual nature - Trnka, Jakub; Drobnik, Jarosław; Susło, Robert (Przewodnik Lekarza/Guide for GPs, 2009)
In the family doctor’s practice there can appear not only patients who suffer from autonomous illnesses, but also the victims of various accidents and crimes. To a special category of patients belong people who are victims of crimes of a sexual nature. These patients demand special care. Such conduct embraces collecting the anamnesis oriented on the circumstances of the incident, the medical examination including making notes on traces of offences, the protection of possible biological material for the purposes of further research, and discussing with the patient the recommendations regarding further proceedings. All the information obtained during the medical examination and its findings must be put in a note in the medical documentation. This is very important, because one can argue that the family doctor is the only doctor who comes into contact with this patient shortly after the incident, and the medical examination documented by him will deliver very important material for the police in the criminal proceedings.